2014
DOI: 10.1038/nrendo.2014.170
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia in diabetes mellitus: epidemiology and clinical implications

Abstract: Hypoglycaemia is a frequent adverse effect of treatment of diabetes mellitus with insulin and sulphonylureas. Fear of hypoglycaemia alters self-management of diabetes mellitus and prevents optimal glycaemic control. Mild (self-treated) and severe (requiring help) hypoglycaemia episodes are more common in type 1 diabetes mellitus but people with insulin-treated type 2 diabetes mellitus are also exposed to frequent hypoglycaemic events, many of which occur during sleep. Hypoglycaemia can disrupt many everyday ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
347
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(368 citation statements)
references
References 124 publications
7
347
0
14
Order By: Relevance
“…Estimates of severe hypoglycemia (defined as the need for third-party assistance) in type 1 diabetes (T1DM) vary from 0.98 to 3.2 episodes per patient per year, affecting 22-46% of patients over a 12-month period [1]. Landmark trials such as the DCCT in T1DM [2] and UKPDS in type 2 diabetes (T2DM) demonstrated that improved glucose control leads to a clear reduction in microvascular complications in the medium/long term and a probable reduction in macrovascular disease in the long term but at the expense of an increase in hypoglycemia rates [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of severe hypoglycemia (defined as the need for third-party assistance) in type 1 diabetes (T1DM) vary from 0.98 to 3.2 episodes per patient per year, affecting 22-46% of patients over a 12-month period [1]. Landmark trials such as the DCCT in T1DM [2] and UKPDS in type 2 diabetes (T2DM) demonstrated that improved glucose control leads to a clear reduction in microvascular complications in the medium/long term and a probable reduction in macrovascular disease in the long term but at the expense of an increase in hypoglycemia rates [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Alterações de equilíbrio, coordenação, visão e nível de consciência decorrentes da hipoglicemia podem precipitar quedas e ferimentos [48][49][50] .…”
Section: Etapa 1: Caracterização Do Evento Agudo De Saúdeunclassified
“…As well as accidents and physical injury, the sequelae of hypoglycemia involve neurologic and cardiovascular complications discussed above [39]. Although reported rates of hypoglycemia in clinical trials vary considerably because of differences in study design, definitions used, and population included (among other factors) [40], a recent nonrandomized retrospective study using real-world outcomes from patients treated with Gla-100 or IDet in the United States suggested a rate of hypoglycemia of ~8% [41].…”
Section: Hypoglycemia In T2dmmentioning
confidence: 99%